Inadvertent Intrafacet Injection during Lumbar Interlaminar Epidural Steroid Injection: A Comparison of CT Fluoroscopic and Conventional Fluoroscopic Guidance - Kranz, P.G. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Inadvertent intrafacet injection can occur during interlaminar epidural steroid injection, resulting in a false-positive loss of resistance and nontarget injection of medication. The purpose of this investigation was to compare the observed rates of this phenomenon during lumbar interlaminar epidural steroid injection performed by using conventional fluoroscopic and CT fluoroscopic guidance. MATERIALS AND METHODS: We retrospectively reviewed 349 lumbar interlaminar epidural steroid injections performed by using conventional fluoroscopy or CT fluoroscopic guidance to determine the observed rates of inadvertent intrafacet injection with each technique. Cases of inadvertent intrafacet injection were classified as either recognized or unrecognized by the proceduralist at the time of the procedure. Multivariate logistic regression was used to determine the independent effect of imaging guidance technique, age, and sex. RESULTS: The rate of inadvertent intrafacet injection was observed to be 7.5% in the CT fluoroscopic group and 0.75% in the conventional fluoroscopy group. All 16 cases identified from CT fluoroscopic procedures were recognized during the procedure; the single case identified from conventional fluoroscopy procedures was not recognized prospectively. The type of imaging guidance showed a statistically significant effect on the detection of the phenomenon (OR for conventional fluoroscopy versus CT fluoroscopy = 0.10, P = .03) that was independent of differences in age or sex. CONCLUSIONS: Inadvertent intrafacet injection is identified during CT fluoroscopic–guided interlaminar epidural steroid injection at a rate that is 10-fold greater than the same procedure performed under conventional fluoroscopy guidance.